Effect of Composted Greenwaste and Rockwool on Plant Growth of Okra, Tomato, and Chili Peppers. Issue 4 (2nd October 2018) - Reddy, Namratha; Crohn, David M.
Abstract: Rockwool is an inert growing media popular in the hydroponics industry. Eventually the rockwool fills with plant material and must be replaced and the residuals are disposed. Composting of this material will conserve landfill space. Although the rockwool itself is stable, roots and other plant materials remaining after harvest can decompose. We studied the effect of composting greenwaste feedstock mixed with spent rockwool in the amount of 10% volume on plant growth. A greenhouse experiment was conducted with two types of soils: sandy loam and clay, each with and without rockwool, and applied at rates 0, 25, 50, and 100 t ha −1 to pots which were then seeded with okra, tomato, or chili pepper. Results indicate that plant growth of all three crops was unaffected by the presence of (10% volume) spent rockwool in the compost. In all cases, increase in application rate of compost enhanced plant growth significantly. While the growth of tomato was unaffected by soil type, shoot weights of okra and chili pepper plants were significantly lower in sandy soil compared to clay loam soil.